BUSINESS E-COMMERCE THROUGH THE INTERNET IN THE PERSPECTIVE OF ISLAMIC LAW IN MAKASSAR (International Conference on Social and Islamic Studies, 2022)
E-commerce is a system built with the aim of increasing efficiency and effectiveness in doing business by utilizing information technology (internet) to improve the quality of products or services and information and reduce unnecessary costs so that the prices of products and information can be reduced in such a way appearance without compromising on quality. The results of this study show that e-commerce via the internet is currently growing rapidly. The process of implementing e-commerce in the city of Makassar has been running in accordance with the dynamics and development of IT technology. From a number of procedures for carrying out e-commerce research in the city of Makassar, it is supported by the data that the authors found, if it is associated with an Islamic legal perspective by being associated with the terms and pillars of buying and selling stipulated in Islamic contract law based on the theory put forward by the Islamic law experts include Syatibi in the theory of maqasid al-Syariah, Ibn Qayim al-jauziy in his theory of change, al-Gazali in the theory of maslah mursalah and lowrance with his theory of change, because e-commerce did not exist at the time of the prophets, companions, and tabi-tabiin, at this time, the authors make ijtihad to establish/instigate the formulation of e-commerce that e-commerce is halal or permissible according to Islamic law, because there is no argument showing its prohibition, even e-commerce can be considered sunnah if it fulfills terms and conditions of sale and purchase. Second, e-commerce is illegal if it conflicts with normative values ​​(the Koran and sunnah, moral values ​​and social values) such as; sex transactions, online, drugs, games that indulge in lust, and the like.